2016
DOI: 10.4172/2157-7110.1000540
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Processing Methods of Cheka: A Traditional Fermented Beverage in Southwestern Ethiopia

Abstract: Cheka is a cereal and vegetable-based beverage which is commonly consumed in Southwestern parts of Ethiopia particularly in Dirashe and Konso. In this study, the traditional processing methods, types and proportions of ingredients, equipments, and sources of energy, economic and socio-cultural importance of cheka were described. In the study areas, maize, sorghum and vegetables such as cabbage, moringa, decne and taro were reported to be utilized for cheka preparation. Informants described the characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…Worku, Woldegiorgis, and Gemeda (2015) indicated that most people particularly adults' start drinking it early on an empty stomach and people in Konso on average drink 3-5 L of cheka per day but in Dirashe adults can drink up to 8 L per day. In these areas, people of all ages including infants, pregnant, and lactating women drink cheka.…”
Section: Chekamentioning
confidence: 99%
See 1 more Smart Citation
“…Worku, Woldegiorgis, and Gemeda (2015) indicated that most people particularly adults' start drinking it early on an empty stomach and people in Konso on average drink 3-5 L of cheka per day but in Dirashe adults can drink up to 8 L per day. In these areas, people of all ages including infants, pregnant, and lactating women drink cheka.…”
Section: Chekamentioning
confidence: 99%
“…The ingredients and methods of preparation of cheka slightly differ from place to place (Hailemariam, F I G U R E 7 Flowchart for cheka preparation in most part of southern nations 2017; Worku et al, 2015). The ingredients and methods of preparation of cheka slightly differ from place to place (Hailemariam, F I G U R E 7 Flowchart for cheka preparation in most part of southern nations 2017; Worku et al, 2015).…”
Section: Chekamentioning
confidence: 99%
“…Cheka is a cereal and vegetable based fermented beverage which is consumed in Southwestern parts of Ethiopia mainly in Dirashe and Konso [7]. The ingredients and methods of preparation of Cheka in different places has a slight difference [8].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Brewers in Dirashe use the root part of "taro", where as producers in Konso only from main ingredients. In some localities, few households also use dried edible left overs of "injera, kitta or kurkufa" [7]. Today Cheka is found almost in all parts of southern Ethiopia due to its high energy supply to do hard works, easily availability of its ingredients and low cost [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation